Oxidative Stress: Ultrasound Detection of Regional Oxidative Stress in Deep Tissues Using Novel Enzyme Loaded Nanoparticles (Adv. Healthcare Mater. 5/2017). Issue 5 (March 2017) - Olson, Emilia S.; Ortac, Inanc; Malone, Christopher; Esener, Sadik; Mattrey, Robert
Abstract : Inanc Ortac, Emilia S. Olson, Robert Mattrey, and co‐workers introduce an intravenously injectable probe labeling sites of oxidative injury in vivo in article number 1601163. The probe they develop is a nanoparticle platform enzymatically catalyzing H2 O2 to water and oxygen producing microbubbles detectable by a clinical ultrasound system. They demonstrate the functionality of 200 nm nanoparticles in vivo in rat ischemic renal injury (IRI) model.